The tumour microenvironment and metabolism in renal cell carcinoma targeted or immune therapy. Issue 3 (11th August 2020) - Lai, Yongchang; Tang, Fucai; Huang, Yapeng; He, Chengwu; Chen, Chiheng; Zhao, Jiquan; Wu, Wenqi; He, Zhaohui
Abstract: Renal cell carcinoma (RCC) is one of the most common tumours of the urinary system, and is insidious and not susceptible to chemoradiotherapy. As the most common subtype of RCC (70–80% of cases), clear cell renal cell carcinoma (ccRCC) is characterized by the loss of von Hippel–Lindau and the accumulation of robust lipid and glycogen. For advanced RCC, molecular‐targeted drugs, tyrosine kinase inhibitors (TKIs) and the immune checkpoint inhibitors (ICIs) have been increasingly recommended and investigated. Due to the existence of a highly dynamic, adaptive and heterogeneous tumour microenvironment (TME), and due to the glucose and lipid metabolism in RCC, this cancer may be accompanied by various types of resistance to TKIs and ICIs. With the increased production of lactate, nitric oxide, and other new by‐products of metabolism, novel findings of the TME and key metabolic enzymes drived by HIF and other factors have been increasingly clarified in RCC carcinogenesis and therapy. However, there are few summaries of the TME and tumour metabolism for RCC progression and therapy. Here, we summarize and discuss the relationship of the important implicated characteristics of the TME as well as metabolic molecules and RCC carcinogenesis to provide prospects for future treatment strategies to overcome TME‐related resistance in RCC. Abstract : Due to the existence of a highly dynamic, adaptive and heterogeneous tumour microenvironment (TME), and due to the glucose and lipid metabolism in Renal cell carcinoma (RCC), this cancer may be accompanied by various types of resistance to tyrosine kinase inhibitors (TKIs) and the immune checkpoint inhibitors (ICIs). With the increased production of lactate, nitric oxide, and other new by‐products of metabolism, novel findings of the TME and key metabolic enzymes drived by HIF and other factors have been increasingly clarified in RCC carcinogenesis and therapy. Here, we summarize and discuss the relationship of the important implicated characteristics of the TME as well as metabolic molecules and RCC carcinogenesis to provide prospects for future treatment strategies to overcome TME‐related resistance in RCC.